INTEGRASI PRINSIP ISLAM DAN HAM DALAM MEWUJUDKAN EKOSISTEM E-COMMERCE BERKEADILAN DI ERA DIGITAL - Khulafi Ahdian; Alhaq; Suhibbullah; Suweknyo (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study develops an integrative conceptual framework for constructing a just e-commerce ecosystem by synthesizing maqasid al-shariah principles and contemporary human rights standards. Employing a normative legal approach with systematic comparative analysis, the study identifies substantive convergence between Islamic principles of justice truthfulness (ṣidq), transparency (tabligh), prohibition of exploitation, and orientation toward maṣlaḥah and human rights principles emphasizing human dignity, non-discrimination, and access to justice. The scholarly contribution of this article lies in proposing a five-pillar model of just e-commerce, consisting of adaptive regulation, effective enforcement mechanisms, voluntary industry standards, public empowerment, and accessible dispute resolution mechanisms. This model addresses structural challenges in digital commerce, including information asymmetry, algorithmic discrimination, and inadequate protection for vulnerable stakeholders, while underscoring the need for e-commerce governance grounded in Islamic values and human rights norms.